Pemanfaatan Instagram Sebagai Media Komunikasi Pemasaran Di Era Digital Pada Akun Instagram @thriftworld_Store - Saputra, Riko Chandra; Prathisara, Gibbran (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study analyzes the use of Instagram as a marketing communication medium on the @thriftworld_store account, a secondhand brand clothing store. The main problem studied is how digital marketing communication strategies can increase brand awareness and encourage increased sales. The purpose of this study is to understand the effectiveness of Instagram as a digital marketing tool for thrift store businesses. This study uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, documentation, and literature studies. Data analysis techniques refer to the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study show that @thriftworld_store actively optimizes various Instagram features, such as stories, reels, and ads, and implements visual-based marketing strategies, customer interaction, and collaboration with influencers. With this strategy, Instagram has proven to be an effective platform in building brand awareness and increasing customer engagement. This study provides recommendations for businesses in optimizing social media as a more effective and efficient marketing strategy.